Chinese Pure Land Buddhism Understanding a Tradition of Practice - Jones, Charles Brewer 1957- (Pure Land Buddhist Studies, 2019)
Chinese Pure Land Buddhism: Understanding a Tradition of Practice is the first book in any western language to provide a comprehensive overview of Chinese Pure Land Buddhism. Even though Pure Land Buddhism was born in China and currently constitutes the dominant form of Buddhist practice there, it has previously received very little attention from western scholars. In this book, Charles B. Jones examines the reasons for the lack of scholarly attention and why the few past treatments of the topic missed many of its distinctive features. He argues that the Chinese Pure Land tradition, with its characteristic promise of rebirth in the Pure Land to even non-elite or undeserving practitioners, should not be viewed from the perspective of the Japanese Pure Land tradition, which differs greatly.